Thermodynamic analysis of a gas turbine engine with a rotating detonation combustor. (1st June 2017) - Sousa, Jorge; Paniagua, Guillermo; Collado Morata, Elena
Highlights: Thermodynamic analysis of thermal power plants with pressure gain combustion. Time-resolved numerical model of rotating detonation combustor. Method of characteristic model of supersonic turbines. Guidance to select range of operation of gas turbines with pressure gain combustion. Gas turbine design trade-off between deflagration and detonation combustors. Abstract: A rotating detonation combustor is a form of "pressure gain combustion" where one or more detonations continuously travel around an annular channel. Pressure gain combustion is a prospective technology being explored to advance gas turbine power plants. These thermodynamic cycles could potentially deliver a performance increase of 20% beyond the current state of the art. However, the combustor operates at extremely unsteady harsh conditions, and the integration of the combustor with the turbomachinery represent unprecedented aero-thermo-structural challenges. At a given instant each stream line experiences a different compression process through the combustor. In contrast to conventional combustors, where a steady approach is valid, in rotating detonation engines the flow particles entering the compressor will be exposed to different processes depending on the relative position of the rotor shaft to the detonation front. Hence, the overall performance assessment requires the development of ad-hoc tools suitable for this new class of combustors, and the modeling of the turbine exposed to supersonic pulsating flows. This paper presents a numerical tool to evaluate precisely the thermodynamic and non-isentropic processes across the entire engine. The NASA's Toolbox for the Modeling and Analysis of Thermodynamic Systems was used to implement new libraries to help us quantify the benefits of a rotating detonation engine versus the conventional technology equipped with constant pressure combustion. The new developed libraries, based on sets of physics-based principles, replicate the engine components performance. This model should allow the optimization of components with respect to energy availability to enable optimal engine sizing and operation. Finally, the paper presents the pressure ratios for which the rotating detonation based engine outperforms the conventional power plants based on the Brayton cycle.